Aspectos clássicos de teorias de segunda ordem - Pompéia, P. J [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
In this work, classical and semiclassical aspects of second order theories were analyzed. First the formulation of a gauge theory for systems whose Lagrangian for the gauge field depends on the field itself and its first and second derivatives was proposed. Applications of this structuire for the U(1) group - Podolsky generalized electodynamics - and for SU(N) - Alekseev, Abuzov e Baikov effective Lagrangian - were made. The Lorentz group SO(3,1) was also analyzed and an isotropic and static solution in linear approximation was obtained for a particular case. Next it was analyzed how Podolsky thory could be constrainedin three different ways using experimetnal data available on the literature. Finally the non-relativistic limits of Podolsky electrodyamics were analyzed on the 5-dimensional galilean formalism. The electric and magnetic limits were obtained

Neste trabalho foram estudados aspectos clássicos de teorias de segunda ordem. Primeiramente foi feita a formulação da teoria de gauge para sistemas em que a Lagrangiana do campo de gauge depende de suas componentes e se suas derivadas primeira e segunda aplicações desta estrutura para os casos U(1) - a eletrodinâmica generalizada de Podolsky - e SU(N) - Lagrangiana efetiva de Alekseev, Abuzov e Baikov. O uso desta estrutura para o caso do grupo de Lorentz SO(3,1) foi feito em separado e uma análise da solução estática e isotrópica no regime linear foi conduzida para um caso particular. Na sequência, analisou-se como a teoria de Podolsky poderia ser vinculada de três maneiras distintas, a partir de dados experimentais disponíveis na literatura. Finalmente, estudou-se regimes não relativísticos da eletrodinâmica de Podolsky, utilizando-se o formalismo galileanoem 5 dimensões. Os limites elétrico e magnético da teoria foram analisados
Keywords: Campos de calibre (Física); Gravitação; Eletrodinamica; Gauge fields (Physics)